The Impact of Depression on Self–Other Discrepancies in Decision Making. (2nd September 2014) - Garcia‐Retamero, Rocio; Okan, Yasmina; Maldonado, Antonio
ABSTRACT Although there is a small but growing body of literature on how people make risky decisions for others and predict others' decisions, results seem to be contradictory. The authors contribute to the understanding of these mixed results by investigating how depression affects self–other discrepancies in decision making and the psychological processes that underlie these discrepancies. In an experiment, depressed and nondepressed individuals read a series of scenarios involving decisions about health, money, and interpersonal relationships. They then indicated which of two options they would choose for themselves or for another person, or predicted which option this person would choose for himself or herself. Finally, participants reported benefits and drawbacks of the decisions (i.e., cognitions) and feelings about risk. Depressed individuals were less prone to bias when they predicted others' decisions than nondepressed individuals. Feelings about risk played a key role in determining the direction and the magnitude of this bias. In contrast, both depressed and nondepressed individuals showed bias when they made decisions for others. This bias affected their decisions in opposing ways and was determined by cognitions. This bias is consistent with literature showing that depression is associated with an increased sensitivity to social risks. The authors provide a theoretical explanation of self–other discrepancies in decision making in depressed and nondepressed individuals and conclude that the results support the assumption that depression is associated with psychological processes whose role is to increase sensitivity to social threats rather than with a more general negative bias in cognitive functioning. Copyright © 2014 John Wiley & Sons, Ltd.